2018
DOI: 10.1016/j.scitotenv.2018.06.158
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic transport model for quantification of norovirus internalization in lettuce from irrigation water and associated health risk

Abstract: Food production using recycled wastewater offers a sustainable way forward in light of limited freshwater resources. However, concerns of food safety should be addressed to protect public health. To this end, we developed a dynamic transport model to track norovirus from the irrigation water to the root and shoot of lettuce during the growth period. These processes were embodied in a system of ordinary differential equations that also incorporated plant growth, transpiration rate, viral attachment and detachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…A norovirus dose-response model based upon PCR-detected viral genome was developed and adopted in the risk analysis of stormwater harvesting for household uses and food crop irrigation [143]. They also showed the risk of viral transport from irrigation water through plant roots to edible portions even without direct contact with irrigation water [144]. Moreover, previous research showed that pathogen dose is the most sensitive parameter in the risk outcome [144].…”
Section: Qmramentioning
confidence: 99%
See 1 more Smart Citation
“…A norovirus dose-response model based upon PCR-detected viral genome was developed and adopted in the risk analysis of stormwater harvesting for household uses and food crop irrigation [143]. They also showed the risk of viral transport from irrigation water through plant roots to edible portions even without direct contact with irrigation water [144]. Moreover, previous research showed that pathogen dose is the most sensitive parameter in the risk outcome [144].…”
Section: Qmramentioning
confidence: 99%
“…They also showed the risk of viral transport from irrigation water through plant roots to edible portions even without direct contact with irrigation water [144]. Moreover, previous research showed that pathogen dose is the most sensitive parameter in the risk outcome [144]. Therefore, to improve the accuracy of risk estimations, the data in gaps in viral concentrations in treated wastewater and dose-response models incorporating multiple pathogens should be addressed.…”
Section: Qmramentioning
confidence: 99%
“…Os resultados mostraram que a alface hidropônica apresenta um maior risco de presença de Norovírus do que a cultivada em solo, porém em ambos os casos, o risco não atendeu ao preconizado e estabelecido pela EPA(Agência de Proteção Ambiental dos Estados Unidos) e pela OMS (Organização Mundial de Saúde). A análise revelou, ainda, que o tempo de colheita e tempo de irrigação influenciam as cargas virais em alface(CHANDRASEKARAN;JIANG, 2018). Outro estudo caracterizou a concentração e remoção de Norovírus Genogrupo II em águas residuais em duas estações de água do norte da Espanha a fim de desenvolver uma avaliação de risco microbiano para gastroenterite viral ocasionada por Norovírus Genogrupo II associada à ingestão de alface irrigada com água desses efluentes.…”
unclassified